Sulcal, ventricular, and white matter changes at MR imaging in the aging brain: data from the cardiovascular health study. - Yue, N C; Arnold, A M; Longstreth, W T; Elster, A D; Jungreis, C A; O'Leary, D H; Poirier, V C; Bryan, R N (Radiology, 1997)
PURPOSE: To determine the distribution of changes in sulcal size, ventricular size, and white matter signal intensity depicted on cranial magnetic resonance (MR) images, with stratification according to age, race, and sex. MATERIALS AND METHODS: Ventricular size, sulcal size, and white matter signal intensity changes were graded on cranial MR images of 3,660 community-living, elderly participants in the Cardiovascular Health Study. A healthier subgroup was also defined. Summary statistics for both groups were generated for age, race, and sex. RESULTS: Regression models of the entire imaged cohort showed higher grades of all variables with increasing age, and higher ventricular and sulcal grades in men and in nonblack individuals. White matter grade was greater in women and in black individuals. Regression models of the healthier subgroup showed similar associations, except for a lack of association of sulcal and ventricular size with race. CONCLUSION: Sulcal width, ventricular size, and white matter signal intensity change with age, sex, and race. Knowledge of these changes is important in appropriate interpretation of MR images of the elderly.
Keywords: Aged; Aged, 80 and over; Aging; Brain; Cardiovascular Diseases; Cerebral Ventricles; Cohort Studies; Continental Population Groups; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Reproducibility of Results; Sex Factors

Left ventricular diastolic filling in the elderly: the cardiovascular health study. - Gardin, J M; Arnold, A M; Bild, D E; Smith, V E; Lima, J A; Klopfenstein, H S; Kitzman, D W (Am J Cardiol, 1998)
Changes in left ventricular (LV) diastolic function (e.g., as measured by transmitral flow velocity) are known to occur with aging. In addition, impaired LV diastolic function plays an important role in such cardiovascular disorders common in the elderly as hypertension, ischemic heart disease, and congestive heart failure (CHF). Participants in the Cardiovascular Health Study, a multicenter study of community-dwelling men (n=2,239) and women (n=2,962) > or = 65 years of age, underwent an extensive baseline evaluation, including echocardiography. Early diastolic LV Doppler (transmitral) peak filling velocity decreased, and peak late diastolic (atrial) velocity increased with age in multivariate analyses (all p <0.001). Early and late diastolic peak filling velocities were both significantly higher in women than in men, even after adjustment for body surface area (or height and weight). In multivariate models in the entire cohort and a healthy subgroup (n=703), gender, age, heart rate, and blood pressure (BP) were most strongly related to early and late diastolic transmitral peak velocities. Early and late diastolic peak velocities both increased with increases in systolic BP and decreased with increases in diastolic BP (p <0.001). Doppler transmitral velocities were compared among health status subgroups. In multiple regression models adjusted for other covariates, and in analysis of variance models examining differences across subgroups adjusted only for age, the subgroup with CHF had the highest early diastolic peak velocities. All clinical disease subgroups had higher late diastolic peak velocities than the healthy subgroup, with the subgroups with either CHF or hypertension having the highest age-adjusted means. The subgroup with hypertension had the lowest ratio of early-to-late diastolic peak velocity, and men with CHF had the highest ratio. These findings are consistent with previous reports that hypertensive subjects exhibit an abnormal relaxation pattern, whereas patients with CHF develop a pattern suggestive of an increased early diastolic left atrial-LV pressure gradient.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Blood Flow Velocity; Cardiovascular Diseases; Cohort Studies; Diastole; Echocardiography, Doppler; Electrocardiography; Female; Health Status; Heart Ventricles; Humans; Male; Ventricular Function, Left

The relationship of fibrinogen and factors VII and VIII to incident cardiovascular disease and death in the elderly: results from the cardiovascular health study. - Tracy, R P; Arnold, A M; Ettinger, W; Fried, L; Meilahn, E; Savage, P (Arterioscler Thromb Vasc Biol, 1999)
Little is known about the prospective associations of fibrinogen, factor VII, or factor VIII with cardiovascular disease (CVD) and mortality in the elderly. At baseline in the Cardiovascular Health Study (5888 white and African American men and women; aged >/=65 years), we measured fibrinogen, factor VIII, and factor VII. We used sex-stratified stepwise Cox survival analysis to determine relative risks (RRs) for CVD events and all-cause mortality (up to 5 years of follow-up), both unadjusted and adjusted for CVD risk factors and subclinical CVD. After adjustment, comparing the fifth quintile to the first, fibrinogen was significantly associated in men with coronary heart disease events (RR=2.1) and stroke or transient ischemic attack (RR=1.3), and also with mortality within 2.5 years of follow-up (RR=5.8) and later (RR=1.7). Factor VIII was significantly associated in men with coronary heart disease events (RR=1.5) and mortality (RR=1.8), and in women with stroke/transient ischemic attack (RR=1.4). For both factors, values were higher in those who died, whether causes were CVD-related or non-CVD-related, but highest in CVD death. Factor VII exhibited associations with incident angina (RR=1.44) in men and with death in women (RR, middle quintile compared with first=0.66). However, in general, factor VII was not consistently associated with CVD events in this population. We conclude that, if confirmed in other studies, the measurement of fibrinogen and/or factor VIII may help identify older individuals at higher risk for CVD events and mortality.
Keywords: Aged; Cardiovascular Diseases; Factor VII; Factor VIII; Female; Fibrinogen; Humans; Male; Multivariate Analysis; Risk Factors

Clinical correlates of ventricular and sulcal size on cranial magnetic resonance imaging of 3,301 elderly people. The Cardiovascular Health Study. Collaborative Research Group. - Longstreth, W T; Arnold, A M; Manolio, T A; Burke, G L; Bryan, N; Jungreis, C A; O'Leary, D; Enright, P L; Fried, L (Neuroepidemiology, 2000)
To identify potential risk factors for and clinical manifestations of ventricular and sulcal enlargement on cranial magnetic resonance imaging (MRI), 3,301 community-dwelling people 65 years or older without a history of stroke or transient ischemic attack underwent extensive standardized evaluations and MRI. In the multivariate model, increased age and white matter grade on MRI were the dominant risk factors for ventricular and sulcal grade. For ventricular grade, other than race, for which non-Blacks had higher grades, models for men and women shared no other factors. For sulcal grades, models for men and women shared variables reflecting cigarette smoking and diabetes. Clinical features were correlated more strongly with ventricular than sulcal grade and more strongly for women than men. Significant age-adjusted correlations between ventricular grade and the Digit-Symbol Substitution Test were found for men and women. Prospective studies will be needed to extend findings of this cross-sectional analysis.
Keywords: Age Distribution; Age Factors; Aged; Aging; Cerebral Ventricles; Continental Population Groups; Cross-Sectional Studies; Diabetes Complications; Female; Humans; Hypertrophy; Linear Models; Magnetic Resonance Imaging; Male; Multivariate Analysis; Risk Factors; Severity of Illness Index; Sex Distribution; Sex Factors; Smoking; Stroke

Predictors of congestive heart failure in the elderly: the Cardiovascular Health Study. - Gottdiener, J S; Arnold, A M; Aurigemma, G P; Polak, J F; Tracy, R P; Kitzman, D W; Gardin, J M; Rutledge, J E; Boineau, R C (J Am Coll Cardiol, 2000)
OBJECTIVES: We sought to characterize the predictors of incident congestive heart failure (CHF), as determined by central adjudication, in a community-based elderly population. BACKGROUND: The elderly constitute a growing proportion of patients admitted to the hospital with CHF, and CHF is a leading source of morbidity and mortality in this group. Elderly patients differ from younger individuals diagnosed with CHF in terms of biologic characteristics. METHODS: We analyzed data from the Cardiovascular Health Study, a prospective population-based study of 5,888 elderly people >65 years old (average 73 +/- 5, range 65 to 100) at four locations. Multiple laboratory measures of cardiovascular structure and function, blood chemistries and functional assessments were obtained. RESULTS: During an average follow-up of 5.5 years (median 6.3), 597 participants developed incident CHF (rate 19.3/1,000 person-years). The incidence of CHF increased progressively across age groups and was greater in men than in women. On multivariate analysis, other independent predictors included prevalent coronary heart disease, stroke or transient ischemic attack at baseline, diabetes, systolic blood pressure (BP), forced expiratory volume 1 s, creatinine >1.4 mg/dl, C-reactive protein, ankle-arm index <0.9, atrial fibrillation, electrocardiographic (ECG) left ventricular (LV) mass, ECG ST-T segment abnormality, internal carotid artery wall thickness and decreased LV systolic function. Population-attributable risk, determined from predictors of risk and prevalence, was relatively high for prevalent coronary heart disease (13.1%), systolic BP > or =140 mm Hg (12.8%) and a high level of C-reactive protein (9.7%), but was low for subnormal LV function (4.1%) and atrial fibrillation (2.2%). CONCLUSIONS: The incidence of CHF is high in the elderly and is related mainly to age, gender, clinical and subclinical coronary heart disease, systolic BP and inflammation. Despite the high relative risk of subnormal systolic LV function and atrial fibrillation, the actual population risk of these for CHF is small because of their relatively low prevalence in community-dwelling elderly people.
Keywords: Aged; Aged, 80 and over; Coronary Disease; Female; Geriatric Assessment; Heart Failure; Humans; Ischemic Attack, Transient; Male; Prospective Studies; Risk Factors; Survival Rate

Cardiovascular disease and mortality in older adults with small abdominal aortic aneurysms detected by ultrasonography: the cardiovascular health study. - Newman, A B; Arnold, A M; Burke, G L; O'Leary, D H; Manolio, T A (Ann Intern Med, 2001)
BACKGROUND: Persons with abdominal aortic aneurysm are more likely to have a higher prevalence of risk factors for and clinical manifestations of cardiovascular disease. It is unknown whether these factors explain the high mortality rate associated with abdominal aortic aneurysm. OBJECTIVE: To describe the risk for mortality, cardiovascular mortality, and cardiovascular morbidity in persons screened for abdominal aortic aneurysm. DESIGN: Longitudinal cohort study. SETTING: Four communities in the United States. PARTICIPANTS: 4734 men and women older than 65 years of age recruited from Medicare eligibility lists. MEASUREMENTS: Abdominal ultrasonography was used to measure the aortic diameter and the ratio of infrarenal to suprarenal measurement of aortic diameter in 1992-1993. Abdominal aortic aneurysm was defined as aortic diameter of 3 cm or greater or infrarenal-to-suprarenal ratio of 1.2 or greater. Mortality, cardiovascular disease mortality, incident cardiovascular disease, and repair or rupture were assessed after 4.5 years. RESULTS: The prevalence of aneurysm was 8.8%, and 87.7% of aneurysms were 3.5 cm or less in diameter. Rates of total mortality (65.1 vs. 32.8 per 1000 person-years), cardiovascular mortality (34.3 vs. 13.8 per 1000 person-years), and incident cardiovascular disease (47.3 vs. 31.0 per 1000 person-years) were higher in participants with aneurysm than in those without aneurysm; after adjustment for age, risk factors, and presence of other cardiovascular disease, the respective relative risks were 1.32, 1.36, and 1.57. Rates of repair and rupture were low. CONCLUSIONS: Rates of total mortality, cardiovascular disease mortality, and incident cardiovascular disease were higher in participants with abdominal aortic aneurysm than in those without aneurysm, independent of age, sex, other clinical cardiovascular disease, and extent of atherosclerosis detected by noninvasive testing. Persons with smaller aneurysms detected by ultrasonography should be advised to modify risk factors for cardiovascular disease while under surveillance for increase in the size of the aneurysm.
Keywords: Aged; Aged, 80 and over; Aortic Aneurysm, Abdominal; Aortic Rupture; Cardiovascular Diseases; Disease Progression; Female; Humans; Incidence; Longitudinal Studies; Male; Mortality; Proportional Hazards Models; Risk Factors; Ultrasonography; United States

Factors associated with healthy aging: the cardiovascular health study. - Burke, G L; Arnold, A M; Bild, D E; Cushman, M; Fried, L P; Newman, A; Nunn, C; Robbins, J (J Am Geriatr Soc, 2001)
OBJECTIVES: To identify factors associated with remaining healthy in older adults. DESIGN: Longitudinal cohort study. SETTING: Data were collected at the four Cardiovascular Health Study field centers. PARTICIPANTS: 5,888 participants age 65 years and older in the Cardiovascular Health Study. MEASUREMENTS: Presence of chronic disease was assessed at baseline and over a maximum 7-year follow-up period. Participants who were free of chronic disease (no cardiovascular disease (CVD), chronic obstructive pulmonary disease, or self-reported cancer, except nonmelanoma skin cancer) at the baseline examination were then monitored for the onset of incident cancer, cardiovascular disease, and fatal outcomes. RESULTS: A high proportion of these older adults was healthy at the initial examination and remained healthy over the follow-up period. Numerous behavioral factors were associated with continued health, including physical activity, refraining from cigarette smoking, wine consumption (women), higher educational status, and lower waist circumference. A number of CVD risk factors and subclinical disease measures were associated with continued health, including higher high-density lipoprotein (HDL) cholesterol, lack of diabetes, thinner common carotid intimal nmedial thickness, lower blood pressure, lower C-reactive protein, and higher ankle-arm blood pressure ratio. Among the behavioral factors, exercise, not smoking, and not taking aspirin remained significant predictors of health even after controlling for CVD risk factors and subclinical disease in older adults. CONCLUSIONS: These data suggest that a number of modifiable behavioral factors (physical activity, smoking, and obesity) and cardiovascular risk factors (diabetes, HDL cholesterol, and blood pressure) are associated with maintenance of good health in older adults.
Keywords: Aged; Aged, 80 and over; Aging; Cardiovascular Diseases; Cohort Studies; Diet; Exercise; Female; Health Status; Humans; Incidence; Life Style; Longitudinal Studies; Lung Diseases, Obstructive; Male; Neoplasms; Probability; Reference Values; Risk Factors; Sex Distribution; Socioeconomic Factors; Survival Rate; United States

Lack of association of the plasminogen activator inhibitor-1 4G/5G promoter polymorphism with cardiovascular disease in the elderly. - Crainich, P; Jenny, N S; Tang, Z; Arnold, A M; Kuller, L H; Manolio, T; Sharrett, A R; Tracy, R P (J Thromb Haemost, 2003)
Elevated circulating plasminogen activator inhibitor-1 (PAI-1) may increase risk of cardiovascular disease (CVD). The 4G allele of the 4G/5G PAI-1 promoter polymorphism is associated with higher levels of PAI-1. We examined the association of PAI-1 4G/5G genotype and CVD events in the elderly participants of the Cardiovascular Health Study (CHS). We measured 4G/5G genotype in a nested case-control study within the CHS. Cases included incident angina, myocardial infarction (MI), and stroke. 4G/5G genotype was not found to be associated with markers of fibrinolysis or CVD risk in the selected elderly cohort. There were no differences in genotype frequencies by case-control status (5G/5G frequency 16-22%; chi2P= 0.07). The 5G allele was not associated with incident CVD events when individuals with at least one 5G allele were compared to 4G/4G homozygotes. The presence of at least one 4G allele was likewise not associated with incident CVD when those with 4G/4G and 4G/5G genotypes were compared to 5G/5G homozygotes. Our results suggest that the PAI-1 4G/5G promoter polymorphism is not associated CVD risk factors or incident CVD events in the elderly.
Keywords: African Continental Ancestry Group; Aged; Alleles; Cardiovascular Diseases; Case-Control Studies; Cohort Studies; European Continental Ancestry Group; Female; Genotype; Homozygote; Humans; Male; Myocardial Infarction; Plasminogen Activator Inhibitor 1; Polymorphism, Genetic; Promoter Regions, Genetic; Risk

Soluble intracellular adhesion molecule-1 is associated with cardiovascular disease risk and mortality in older adults. - Jenny, N S; Arnold, A M; Kuller, L H; Sharrett, A R; Fried, L P; Psaty, B M; Tracy, R P (J Thromb Haemost, 2006)
BACKGROUND: Intracellular adhesion molecule-1 (ICAM-1) regulates leukocyte-endothelial attachment, a process crucial to atherosclerosis. Circulating soluble ICAM-1 (sICAM-1) may serve as a marker of cardiovascular disease (CVD) progression. OBJECTIVES: We examined the association of sICAM-1 with measures of subclinical CVD and risk of incident CVD events and death in older men and women (age > or = 65 years) from the Cardiovascular Health Study. METHODS: Selected participants were free of clinical CVD at baseline. Non-exclusive incident case groups were angina (n = 534), myocardial infarction (n = 304), stroke (n = 327), and death (n = 842; CVD death = 310). A total 643 subjects were free of events during follow-up. RESULTS: sICAM-1 was positively associated with C-reactive protein, interleukin-6 and fibrinogen and measures of subclinical CVD in these older men and women. In Cox regression models adjusted for age, gender, and race, increasing levels of sICAM-1 were associated with increased risk of all cause mortality in men and women. Hazard ratios (95% confidence intervals) for a one standard deviation increase in sICAM-1 (89.7 ng mL(-1)) were 1.3 (1.1-1.4) in men and 1.2 (1.1-1.3) in women. sICAM-1 was associated with increased risk of CVD death in women (1.2; 1.0-1.5), but not men (1.1; 0.9-1.3). There were no associations of sICAM-1 with non-fatal CVD events. CONCLUSIONS: While sICAM-1 was associated with death in older men and women, there was a more marked association between sICAM-1 and CVD death in women.
Keywords: Aged; Aged, 80 and over; Angina Pectoris; Biomarkers; Cardiovascular Diseases; Female; Humans; Incidence; Intercellular Adhesion Molecule-1; Male; Mortality; Myocardial Infarction; Regression Analysis; Risk Factors; Sex Factors; Solubility; Stroke

Concurrent change in dehydroepiandrosterone sulfate and functional performance in the oldest old: results from the Cardiovascular Health Study All Stars study. - Sanders, J L; Cappola, A R; Arnold, A M; Boudreau, R M; Chaves, P H; Robbins, J; Cushman, M; Newman, A B (J Gerontol A Biol Sci Med Sci, 2010)
INTRODUCTION: The correlation between dehydroepiandrosterone sulfate (DHEAS) decline and age led to the hypothesis that DHEAS might be a marker of primary aging, though conflicting data from observational studies of mortality do not support this. We evaluated concurrent DHEAS and functional decline in a very old cohort to test if DHEAS change tracks with functional change during aging. METHODS: DHEAS and functional performance (gait speed, grip strength, Modified Mini-Mental State Examination [3MSE] score, and digit symbol substitution test [DSST] score) were measured in 1996-1997 and 2005-2006 in 989 participants in the Cardiovascular Health Study All Stars study (mean age 85.2 years in 2005-2006, 63.5% women and 16.5% African American). We used multivariable linear regression to test the association of DHEAS decline with functional decline. RESULTS: After adjustment, each standard deviation decrease in DHEAS was associated with greater declines in gait speed (0.12 m/s, p = .01), grip strength (0.09 kg, p = .03), 3MSE score (0.13 points, p < .001), and DSST score (0.14 points, p = .001) in women only. Additional adjustment for baseline DHEAS attenuated the association with grip strength but did not alter other estimates appreciably, and baseline DHEAS was unassociated with functional decline. CONCLUSIONS: In this cohort of very old individuals, DHEAS decline tracked with declines in gait speed, 3MSE score, and DSST score, but not grip strength, in women independent of baseline DHEAS level. DHEAS decline might be a marker for age-associated performance decline, but its relevance is specific to women.
Keywords: Aged, 80 and over; Biomarkers; Cognition; Cohort Studies; Dehydroepiandrosterone Sulfate; Female; Gait; Geriatric Assessment; Hand Strength; Health Surveys; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Sex Factors; United States

Association of heat shock proteins with all-cause mortality. - Broer, L; Demerath, E W; Garcia, M E; Homuth, G; Kaplan, R C; Lunetta, K L; Tanaka, T; Tranah, G J; Walter, S; Arnold, A M; Atzmon, G; Harris, T B; et al. (Age (Dordr), 2013)
Experimental mild heat shock is widely known as an intervention that results in extended longevity in various models along the evolutionary lineage. Heat shock proteins (HSPs) are highly upregulated immediately after a heat shock. The elevation in HSP levels was shown to inhibit stress-mediated cell death, and recent experiments indicate a highly versatile role for these proteins as inhibitors of programmed cell death. In this study, we examined common genetic variations in 31 genes encoding all members of the HSP70, small HSP, and heat shock factor (HSF) families for their association with all-cause mortality. Our discovery cohort was the Rotterdam study (RS1) containing 5,974 participants aged 55 years and older (3,174 deaths). We assessed 4,430 single nucleotide polymorphisms (SNPs) using the HumanHap550K Genotyping BeadChip from Illumina. After adjusting for multiple testing by permutation analysis, three SNPs showed evidence for association with all-cause mortality in RS1. These findings were followed in eight independent population-based cohorts, leading to a total of 25,007 participants (8,444 deaths). In the replication phase, only HSF2 (rs1416733) remained significantly associated with all-cause mortality. Rs1416733 is a known cis-eQTL for HSF2. Our findings suggest a role of HSF2 in all-cause mortality.
Keywords: Aged, 80 and over; Aging; Cause of Death; Forecasting; Genotype; Heat-Shock Proteins; Humans; Longevity; Promoter Regions, Genetic; Retrospective Studies; Transcription, Genetic; United States

Prediction and classification of cardiovascular disease risk in older adults with diabetes. - Mukamal, K J; Kizer, J R; Djoussé, L; Ix, J H; Zieman, S; Siscovick, D S; Sibley, C T; Tracy, R P; Arnold, A M (Diabetologia, 2013)
AIMS/HYPOTHESIS: We sought to derive and validate a cardiovascular disease (CVD) prediction algorithm for older adults with diabetes, and evaluate the incremental benefit of adding novel circulating biomarkers and measures of subclinical atherosclerosis. METHODS: As part of the Cardiovascular Health Study (CHS), a population-based cohort of adults aged ≥65 years, we examined the 10 year risk of myocardial infarction, stroke and cardiovascular death in 782 older adults with diabetes, in whom 265 events occurred. We validated predictive models in 843 adults with diabetes, who were followed for 7 years in a second cohort, the Multi-Ethnic Study of Atherosclerosis (MESA); here 71 events occurred. RESULTS: The best fitting standard model included age, smoking, systolic blood pressure, total and HDL-cholesterol, creatinine and the use of glucose-lowering agents; however, this model had a C statistic of 0.64 and poorly classified risk in men. Novel biomarkers did not improve discrimination or classification. The addition of ankle-brachial index, electrocardiographic left ventricular hypertrophy and internal carotid intima-media thickness modestly improved discrimination (C statistic 0.68; p = 0.002) and classification (net reclassification improvement [NRI] 0.12; p = 0.01), mainly in those remaining free of CVD. Results were qualitatively similar in the MESA, with a change in C statistic from 0.65 to 0.68 and an NRI of 0.09 upon inclusion of subclinical disease measures. CONCLUSIONS/INTERPRETATION: Standard clinical risk factors and novel biomarkers poorly discriminate and classify CVD risk in older adults with diabetes. The inclusion of subclinical atherosclerotic measures modestly improves these features, but to develop more robust risk prediction, a better understanding of the pathophysiology and determinants of CVD in this patient group is needed.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Biomarkers; Blood Pressure; Cardiovascular Diseases; Carotid Intima-Media Thickness; Cholesterol, HDL; Diabetes Mellitus; Female; Humans; Male; Myocardial Infarction; Regression Analysis; Risk Factors; Stroke

Replication of genetic loci for ages at menarche and menopause in the multi-ethnic Population Architecture using Genomics and Epidemiology (PAGE) study. - Carty, C L; Spencer, K L; Setiawan, V W; Fernandez-Rhodes, L; Malinowski, J; Buyske, S; Young, A; Jorgensen, N W; Cheng, I; Carlson, C S; Brown-Gentry, K; Goodloe, R; et al. (Hum Reprod, 2013)
STUDY QUESTION: Do genetic associations identified in genome-wide association studies (GWAS) of age at menarche (AM) and age at natural menopause (ANM) replicate in women of diverse race/ancestry from the Population Architecture using Genomics and Epidemiology (PAGE) Study? SUMMARY ANSWER: We replicated GWAS reproductive trait single nucleotide polymorphisms (SNPs) in our European descent population and found that many SNPs were also associated with AM and ANM in populations of diverse ancestry. WHAT IS KNOWN ALREADY: Menarche and menopause mark the reproductive lifespan in women and are important risk factors for chronic diseases including obesity, cardiovascular disease and cancer. Both events are believed to be influenced by environmental and genetic factors, and vary in populations differing by genetic ancestry and geography. Most genetic variants associated with these traits have been identified in GWAS of European-descent populations. STUDY DESIGN, SIZE, DURATION: A total of 42 251 women of diverse ancestry from PAGE were included in cross-sectional analyses of AM and ANM. MATERIALS, SETTING, METHODS: SNPs previously associated with ANM (n = 5 SNPs) and AM (n = 3 SNPs) in GWAS were genotyped in American Indians, African Americans, Asians, European Americans, Hispanics and Native Hawaiians. To test SNP associations with ANM or AM, we used linear regression models stratified by race/ethnicity and PAGE sub-study. Results were then combined in race-specific fixed effect meta-analyses for each outcome. For replication and generalization analyses, significance was defined at P < 0.01 for ANM analyses and P < 0.017 for AM analyses. MAIN RESULTS AND THE ROLE OF CHANCE: We replicated findings for AM SNPs in the LIN28B locus and an intergenic region on 9q31 in European Americans. The LIN28B SNPs (rs314277 and rs314280) were also significantly associated with AM in Asians, but not in other race/ethnicity groups. Linkage disequilibrium (LD) patterns at this locus varied widely among the ancestral groups. With the exception of an intergenic SNP at 13q34, all ANM SNPs replicated in European Americans. Three were significantly associated with ANM in other race/ethnicity populations: rs2153157 (6p24.2/SYCP2L), rs365132 (5q35/UIMC1) and rs16991615 (20p12.3/MCM8). While rs1172822 (19q13/BRSK1) was not significant in the populations of non-European descent, effect sizes showed similar trends. LIMITATIONS, REASONS FOR CAUTION: Lack of association for the GWAS SNPs in the non-European American groups may be due to differences in locus LD patterns between these groups and the European-descent populations included in the GWAS discovery studies; and in some cases, lower power may also contribute to non-significant findings. WIDER IMPLICATIONS OF THE FINDINGS: The discovery of genetic variants associated with the reproductive traits provides an important opportunity to elucidate the biological mechanisms involved with normal variation and disorders of menarche and menopause. In this study we replicated most, but not all reported SNPs in European descent populations and examined the epidemiologic architecture of these early reported variants, describing their generalizability and effect size across differing ancestral populations. Such data will be increasingly important for prioritizing GWAS SNPs for follow-up in fine-mapping and resequencing studies, as well as in translational research.
Keywords: Age Factors; Cross-Sectional Studies; Female; Genome-Wide Association Study; Genotype; Humans; Menarche; Menopause; Polymorphism, Single Nucleotide